Global burden of aortic aneurysm attributable to high-sodium diet from 1990 to 2021 - Shen, Xiedong; Tian, Weiling; Xue, Chun; Ji, Xiangguo; Qu, Anqi; Lv, Jun (Frontiers in Nutrition, 2025)
BackgroundThis study aims to investigate the impact of high-sodium diet (HSD) on the global burden of aortic aneurysm (AA), analyze its epidemiological trends across different regions, sexes, and age groups, and project future trends.MethodsData were obtained from the Global Burden of Disease Study 2021 (GBD 2021) to assess the disability-adjusted life years (DALYs) and death cases of AA attributable to HSD (AA-HSD) from 1990 to 2021. A decomposition analysis was conducted to quantify the contributions of population growth, aging, and epidemiological changes to the disease burden. The Nordpred model was used to project trends from 2022 to 2045.ResultsFrom 1990 to 2021, the global DALYs cases of AA-HSD increased by 103%, and death cases increased by 120%. The largest increase in DALYs was observed in low-middle Socio-demographic Index (SDI) regions (234%), with South Asia experiencing the most significant rise (361%). Aging and population growth were the main drivers of the increased DALYs and death cases. While high SDI regions bore a heavier disease burden, relative inequality slightly improved. Projections indicate that from 2022 to 2045, both DALYs and death cases will continue to rise, with males experiencing a higher burden than females.ConclusionHSD significantly contribute to the global burden of AA, particularly in low-middle SDI regions. Moving forward, differentiated strategies should be adopted based on regional development levels, such as reinforcing salt-reduction policies, promoting early screening programs.